2013
DOI: 10.1007/s00204-013-1114-5
|View full text |Cite
|
Sign up to set email alerts
|

The isoflavone irilone contributes to the estrogenic potential of dietary supplements containing red clover

Abstract: A recent intervention study demonstrated the occurrence of irilone as second most abundant isoflavone next to daidzein in human plasma after consumption of a red clover-based dietary supplement (RCDS) containing predominately formononetin ≫ biochanin A > irilone (12 % of these isoflavones). To elucidate the relevance of this finding, in the present study (1) the representativeness of the isoflavone composition of the RCDS and (2) the estrogenic activity of irilone were investigated. Thus, major isoflavones wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…As ICI182,780 antagonized the influence of irilone, the estrogen receptor pathway is considered to be the most likely mechanism of irilone activity. [81] In a similar experimental model of MCF-7 cell line, measurements of the estrogenic activity of different batches of red clover demonstrated that both estradiol and red clover extracts increased the proliferation of MCF-7 in a concentration-dependent manner. The estrogenic potency was as follows E2 >>> genistein > biochanin A = daidzein > formononetin and increased with a decline of genistein concentration.…”
Section: Clovers and Menopause-related Disorders: The Newest In-vivo mentioning
confidence: 95%
See 1 more Smart Citation
“…As ICI182,780 antagonized the influence of irilone, the estrogen receptor pathway is considered to be the most likely mechanism of irilone activity. [81] In a similar experimental model of MCF-7 cell line, measurements of the estrogenic activity of different batches of red clover demonstrated that both estradiol and red clover extracts increased the proliferation of MCF-7 in a concentration-dependent manner. The estrogenic potency was as follows E2 >>> genistein > biochanin A = daidzein > formononetin and increased with a decline of genistein concentration.…”
Section: Clovers and Menopause-related Disorders: The Newest In-vivo mentioning
confidence: 95%
“…This interaction was used for the determination of molecular mechanisms of irilone effects on the examined cells. As ICI182,780 antagonized the influence of irilone, the estrogen receptor pathway is considered to be the most likely mechanism of irilone activity . In a similar experimental model of MCF‐7 cell line, measurements of the estrogenic activity of different batches of red clover demonstrated that both estradiol and red clover extracts increased the proliferation of MCF‐7 in a concentration‐dependent manner.…”
Section: Estrogenic Effects Of Trifolium Plantsmentioning
confidence: 96%
“…Irilone (34) was shown to possess α-amylase inhibitory effects which would support antidiabetic action (Ibrahim et al 2017). The same compound (34) could also play a role as phytoestrogen as it was contributing to the oestrogenic activity of red clover extracts ((Lutter et al 2014). Hence, there is remarkable potential of I. adriatica constitutents to be explored further for antiinflammatory, chemopreventive, antidiabetic and phytoestrogenic effects.…”
Section: Quantitative Estimate Of Major Compounds In I Adriatica Rhimentioning
confidence: 99%
“…In these cancers, progesterone acts were associated with positive outcomes and reduced hazard of disease occurrence . 12,13 From the literature survey, it was found that the identification of the structural properties of the molecule under study had not been performed previously in the light of computational chemistry [14][15][16] and hence the study was undertaken. The main aim of the present study is to give a comprehensive description of the electronic properties andspectroscopic (FT-IR and UV-Vis) profiles of the novel antagonist irilone as a progesterone receptor (PR) effect supporter in endometrial and ovarian cancer cell lines by quantum-mechanical (QM) and molecular docking methods.It is believed that the outputs of this study will provide a deep and accurate understanding of the possible biological activities of the title compound.…”
Section: Introductionmentioning
confidence: 99%